EUPHEMISM FOUND IN INSERT TRANS TV INDONESIAN INFOTAINMENT - AGFARINNISA’, HIKMAH NOVIANTI (Jurnal Ilmiah Mahasiswa FIB, 2015)
Key words: Sociolinguistics, euphemism, Insert Trans TV Language has different characteristics to show its uniqueness. The existence of taboo language as one of the characteristics in each language makes the user of the language should be aware of this prohibition. The use of euphemism is not only to dress up the linguistic taboo, but also to express politeness that can be accepted by people. It is used to avoid people saying certain matters directly and rather to say it into other polite words or acceptable words. In this study the writer is interested in analyzing euphemism, which is about using mild language to prevent the harsh language in particular terms. The writer examines euphemistic expressions used by announcers and presenters of Insert Trans TV . This study attempts to answer the two research problems, namely: (1) What types of euphemism are used by announcer and presenter of Insert Indonesia infotainment Trans TV, and (2) What are the motives of announcer and presenter of Insert Indonesia infotainment Trans TV in using euphemism.In analyzing the types of euphemism in this study, the writer uses the theory of Warren (1992). She gives four devices for euphemism formation: word formation devices, phonemic modification, loan words, and semantic innovation. Later in analyzing motives in using euphemism, the writer uses theory of Ullman (1962) where he has three categories of euphemism motives: fear, delicacy fall and propriety. In this study, a qualitative approach is used to analyze the data in the form of transcript containing euphemistic expression used by announcers and presenters of Insert Trans TV.The result shown in the transcript proved that announcers and presenters of Insert Trans TV used several types of euphemism: 4 compounding, 2 acronyms, 1 onomatopea, 1 phonemic replacement, 1 loan word, 1 abbreviation, 7 particularisation, 1 implication, 2 metaphor, 3 metonym, 2 reversal, 5 understatement, 2 overstatement. In addition, the analysis of motives in using euphemistic expressions found in the transcript is 3 motives of fear, 19 motives ofdelicacy fall, and 10 motives of propriety.The writer suggests the next researcher develop this research by using a different object such as novel, movie, and also from daily activity or daily conversation.